Rivaroxaban-Induced Hemorrhage Associated with ABCB1 Genetic Defect - Ing Lorenzini, Kuntheavy; Daali, Youssef; Fontana, Pierre; Desmeules, Jules; Samer, Caroline (Frontiers in Pharmacology, 2016)
We report a patient who presented a non-ST segment elevation myocardial infarction in the context of severe normocytic hypochromic anemia related to gastrointestinal bleeding, 3 months after switching anticoagulant from the vitamin K antagonist acenocoumarol to the direct oral anticoagulant rivaroxaban. High levels of both anti-Xa activity and rivaroxaban plasma concentrations were measured despite rivaroxaban withdrawal, suggesting reduced elimination/drug clearance. Estimated half-life was 2–3 times longer than usually reported. The patient is a homozygous carrier of ABCB1 variant alleles, which could have participated to reduced elimination of rivaroxaban. Furthermore, CYP3A4/5 phenotyping showed moderately reduced enzyme activity. Drug-drug interaction with simvastatin may have contributed to decreased rivaroxaban elimination. Although in the present case moderate acute renal failure probably played a role, more clinical data are required to elucidate the impact of ABCB1 polymorphism on rivaroxaban pharmacokinetics and bleeding complications.